HTLV-1 and HTLV-2 infections significantly alter small RNA expression in asymptomatic carriers - Fernandes, Lorena Abreu; Folgosi, Victor Ângelo; Pessôa, Rodrigo; Assone, Tatiane; Victor, Jefferson Russo; Casseb, Jorge; de Oliveira, Augusto César Penalva; Nukui, Youko; da Silva Duarte, Alberto José; Sanabani, Sabri Saeed (Frontiers in Medicine, 2025)
IntroductionThis study investigates the impact of HTLV-2 infection on small RNA (sRNA) expression profiles, building on previous findings related to HTLV-1.MethodsUsing Illumina Massive Parallel Sequencing, we analyzed sRNA profiles from asymptomatic HTLV-1 and HTLV-2 infected individuals and healthy controls.ResultsOur results reveal significant differential expression of 331 known and 441 novel sRNAs among the groups, including miRNAs, piRNAs, and tRNAs. Notably, distinct clusters of sRNA expression patterns were identified, with specific miRNAs showing significant upregulation or downregulation in HTLV-1 and HTLV-2 infections. Gene Ontology analysis indicated significant involvement of target genes in transcription regulation and RNA-binding processes, while KEGG pathway analysis highlighted enrichment in cancer-related pathways and signaling cascades such as FoxO, Ras, and MAPK. Network analysis identified key miRNAs, such as hsa-miR-20b-5p and hsa-let-7e-5p, as central regulators with extensive interactions, suggesting their potential role in the pathogenesis and immune response of HTLV infections.DiscussionThese findings provide a foundation for future research into the molecular mechanisms of HTLV infections and the development of targeted therapies. The identified sRNAs, especially important miRNAs such as hsa-miR-20b-5p and hsa-let-7e-5p, could serve as potential biomarkers for disease progression or as therapeutic targets to modulate the immune response and disrupt viral pathogenesis. This opens up new avenues for precision medicine in HTLV-associated diseases.